ANTHROPOLOGY OF CULTURAL TRANSFORMATION I: TOGETHERNESS AND SEPARATION (XUDONG ZHAO 2024) - Ariyanto, Komang (UI Scholars Hub, 2025)
The book Anthropology of Cultural Transformation I: Togetherness and Separation by Zhao analyzes cultural change amid globalization and technological advancement. Zhao explores the duality between togetherness and separation in modern social dynamics, demonstrating how cultural identities adapt. Through ethnographic case studies and comparisons with thinkers like Clifford Geertz and Arjun Appadurai, the book invites readers to reflect on the impact of these changes on cultural practices and social cohesion. While Zhao highlights technology's role in fostering connectivity, he also emphasizes the effects of cultural homogenization. This book is relevant for both academics and policymakers who need to support cultural diversity amid global transformation.